Balancing act [noise based sensory enhancement technology]. - Harry, J.D (IEEE spectrum)
Research teams at Afferent Corp. and at Boston University have been collaborating to develop and test a new class of neurotherapy devices that have the promise of directly improving mechanical sensory function to help prevent falls in the elderly and foot injuries and amputations in people with diabetes. These devices are based on the discovery that certain forms of electrical or mechanical stimulation applied to mechanoreceptors increase their ability to detect sensory information. Results show that the best type of stimulation signal is not a finely tuned frequency but rather white noise. When presented with this stimulus over an extended period, the sensory neurons were unable to adapt to it. These findings reinforce the growing body of research that establishes the connection between sensory activity and the ability of the nervous system to repair itself following injury.